DJAMALUDDIN “ADINEGORO” (1904-1967): TOKOH DI BALIK PENGHARGAAN TERTINGGI JURNALISTIK DI INDONESIA - Jauhari, Fadhilah; Umasih; Syukur, Abdul (Program Studi Pendidikan Sejarah Fakultas Ilmu Sosial dan Hukum Universitas Negeri Jakarta, 2021)
Djamaluddin Datuk Maradjo Sutan is an Indonesian Journalism Pioneer from Talawi, West Sumatra. However, he is better known by his pseudonym which leads to the Javanese name Adinegoro. The name Adinegoro itself was immortalized by the Indonesian Journalists Association (PWI) as the name of the highest journalism award in Indonesia since 1974. Making someone's name for an award, of course, that person has an important role in his field. Djamaluddin was the first Indonesian to study journalism directly from his home country, Germany. After returning from Europe, he is always asked or chosen to serve as a leader in a newspaper or magazine in Indonesia. Not only that, his focus on writing abroad, which always captivated readers, made him a journalist who covered the Round Table Conference in The Hague, the Netherlands at the end of 1949. Djamaluddin was also active in giving his views on the nationalization of the Aneta news agency. Djamaluddin's concern is also given to young people who want to study journalism in Indonesia. This study aims to examine the role of Djamaluddin